2021
DOI: 10.3389/fpsyt.2021.654026
|View full text |Cite
|
Sign up to set email alerts
|

ICD-11 Personality Disorders: A Psychodynamic Perspective on Personality Functioning

Abstract: The new ICD-11 introduces a fully dimensional classification of personality disorders representing a fundamental change in personality disorder diagnosis with major implications for clinical practice and research. The new system centers on the evaluation of the severity of impairment in the areas of self and interpersonal functioning. This focus on personality functioning converges with long-standing psychoanalytic/psychodynamic conceptualizations of personality pathology. In a detailed conceptual analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 50 publications
1
16
0
2
Order By: Relevance
“…Criterion A (personality functioning) in DSM-5, at its core, is characterized by basic psychological human capacities in the domains of self (identity, self-direction) and interpersonal relationships (intimacy, empathy; DSM-5, American Psychiatric Association, 2013 ; ICD-11, World Health Organization [WHO], 2019 ; see Caligor and Kernberg, 2005 ; Bender et al, 2011 ; Tyrer et al, 2019 ). Criterion A is generally aligned with broad psychodynamic concepts ( Bender et al, 2011 ; Blüml and Doering, 2021 ), characterized as personality organization or structure of the representations of self and others ( Kernberg, 1967 ; Bender et al, 2011 ; Skodol et al, 2011 ; Pincus et al, 2020 ; Blüml and Doering, 2021 ). Both mentalization and Criterion A attempt to assess the quality of representations as internal mental states of self and others that are considered fundamental to building healthy social relationships and enable adaptations to the social environment ( Fonagy and Luyten, 2018 ; Fonagy et al, 2018 ; Luyten et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Criterion A (personality functioning) in DSM-5, at its core, is characterized by basic psychological human capacities in the domains of self (identity, self-direction) and interpersonal relationships (intimacy, empathy; DSM-5, American Psychiatric Association, 2013 ; ICD-11, World Health Organization [WHO], 2019 ; see Caligor and Kernberg, 2005 ; Bender et al, 2011 ; Tyrer et al, 2019 ). Criterion A is generally aligned with broad psychodynamic concepts ( Bender et al, 2011 ; Blüml and Doering, 2021 ), characterized as personality organization or structure of the representations of self and others ( Kernberg, 1967 ; Bender et al, 2011 ; Skodol et al, 2011 ; Pincus et al, 2020 ; Blüml and Doering, 2021 ). Both mentalization and Criterion A attempt to assess the quality of representations as internal mental states of self and others that are considered fundamental to building healthy social relationships and enable adaptations to the social environment ( Fonagy and Luyten, 2018 ; Fonagy et al, 2018 ; Luyten et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, psychoticism has been found to map borderline pathology in adults in terms of cognitive and perceptual dysregulation, including proneness to dissociation ( 46 , 47 ). Notable, the ICD-11 captures such reality testing features in terms of global severity thus aligning them with functioning ( 1 , 48 , 49 ). In other studies, psychoticism has been found to overlap with internalizing and externalizing components that mark a general tendency of dysfunction in young individuals ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar model has been established in the DSM‑5 AMPD, where the two large domains self and interpersonal functioning are parted in (roughly speaking) perceptual (identity and empathy) and regulatory (self-direction and intimacy) aspects (see Table 1 ). Finally, a model has been proposed for the upcoming ICD-11 ([ 9 ], see also [ 18 ]). To sum up, several contemporary models of personality functioning assume that self-related and other-related affect-laden information processing and regulation capacities make up the basis on which more nuanced personality characteristics operate.…”
Section: The Concept Of Personality Functioning and Structural Integr...mentioning
confidence: 99%